Cosmic Luminous Shock Waves - Bagdoo, Russell (European Journal of Applied Sciences, 2021)
We hypothesize the existence of cosmic luminous shock waves which might participate in the formation of clouds and severe weather events, such as tornadoes, hurricanes. These waves would have the peculiarity to be created and modulated by the shock of galactic cosmic rays and extragalactic gamma rays with the particles of the solar corona: the energetic particles of cosmic rays collide with atoms of the solar atmosphere, shatter them, with the result that the velocity of the ultra-relativistic electron in the solar plasma might be greater than the speed of light in this medium. What, in particular, would produce a secondary radiation of higher intensity analogous to that of the shock waves radiating in liquids by Cherenkov effect. Their existence may be linked to a visual phenomenon called «experience of bright light flashes» with which all the astronauts are confronted. There would be a Cherenkov radiation in higher atmospheric layers and in the solar plasma, similar to that which exists in liquid medium, suitable for modifying the albedo of the planet and strike the eyes of people in space.